If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 63 Reorder the terms: 7 + 3x = 63 Solving 7 + 3x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 63 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 63 + -7 3x = 63 + -7 Combine like terms: 63 + -7 = 56 3x = 56 Divide each side by '3'. x = 18.66666667 Simplifying x = 18.66666667
| 5x+40+135=180 | | 6w^5(3w+2w^3)=0 | | (x+2)(x+2)(x+2)=x^3-2x | | 3x+z=3y | | 4ln(7x)=20 | | -106=9k-7 | | X-y=-23 | | X-y=-27 | | 5x+5+50=90 | | 7=-3*3+2-1 | | 0.4285714285714286x+5=8 | | 5x+1=13+2x | | m^4-256=0 | | 5p-4=7 | | 35-7=3(x-2) | | 4+2+4x+3x=3x+2x+6 | | -9x-4y=1 | | 8-5x-6+9x= | | (x^(-2/3)y^(4/5)z^(3)÷(x^(1/3)y^2))^(-8/15) | | 9-4l=19 | | 12x+8x-15=0 | | (-.5x+35)=0 | | 45-20x= | | k/7-8=-10 | | 8.9=x-9.5 | | -5v-10=50 | | 8t-12=4(2t-3) | | 3x-x^2=20 | | 6i+3=-7 | | P=14*(8/t) | | -8u-15=15 | | -25t+7t^2-12=0 |